Development of highly productive current modes for copper electrowinning as a dense metal - Линючева, Ольга Владимировна; Донченко, Маргарита Ивановна; Ущаповский, Дмитрий Юрьевич; Бык, Михаил Владимирович; Складанный, Денис Николаевич (Eastern-European Journal of Enterprise Technologies, 2014)
Electrochemical studies of copper planting from sulfuric acid solutions, the composition of which varies during the electrowinning process in order to increase its productivity and reduce power consumption for copper production were carried out in the paper. It was found that at reducing the copper sulfate concentration (Cc) from 200 to 40 g/dm2 and increasing acid concentration (Ca) from 30 to 90 g/dm2, the role of migration of copper ions in the mass transfer is low, but the solution acidity does affect the limiting current of copper deposition iL. The dependences of iL on two variables - Cc and Ca were experimentally found and mathematically described, which was the basis for selecting the working current densities (ip) of the copper electrowinning process. The influence of the solution composition and the current density on the cathode copper morphology was investigated. It is shown that the compact deposits without dendrites and powder can be obtained at a ratio of ір/iL=0,825. Electrolysis modes with cathodic current density reduction in time were developed, which allow to combine the high speed of the process, a high metal current efficiency and obtaining a dense copper precipitate with the quality, acceptable for hydrometallurgy. Results and proposed approach to optimizing copper electrowinning parameters can be used in hydrometallurgy for metallic copper production, in processes of copper extraction from production wastes, wastewater purification from metal ions.